Addressing data gaps: implications for preventing domestic homicide - Giesbrecht, Crystal J. (Journal of family violence, 2023)
Purpose: Over a ten-year period (2010–2019), there were 815 victims of intimate partner/domestic homicide (IP/DH) in Canada. Definitions of IP/DH not only shape our understanding of these deaths; they also shape how data are collected as well as policy and prevention efforts. The Canadian Domestic Homicide Prevention Initiative with Vulnerable Populations (CDHPIVP) examined IP/DH with a focus on four specific populations: Indigenous; immigrant and refugee; people living in rural, remote, and northern areas; and children exposed to domestic violence. Not only is the issue of defining IP/DH complex, but complexity also arises in how we define specific populations that experience different risks, barriers, and vulnerabilities to intimate partner violence and IP/DH. Methods: At the conclusion of the CDHPIVP, the authors participated in a panel discussion; this article reports and expands upon that discussion by discussing the availability and accessibility of IP/DH data, including official data sources, court decisions, media reports, and domestic violence death reviews. Results: We provide an overview of available data, as well as data gaps, regarding IP/DH among each of the four populations, as well as available data sources and challenges in data accessibility. Conclusions: We share our priorities for enhancing data to inform researchers, policy-makers, and practitioners who are working toward the prevention of IP/DH. Specifically, we note the importance of partnerships for collecting and working with data and opportunities for enhancing data quality regarding research with each of the four populations.